Role of thermal effect on the capture stability of plasmonic optical tweezers - Yukun Ji; Yatao Ren; Xuehui Wang; Hong Qi (Case Studies in Thermal Engineering)
Plasmonic optical tweezers exhibit excellent potential in the manipulation of nanoparticles, which advances the fields of nano medicine, chemical and biological sensing, and robotics. However, the capture stability of nanoparticles is affected by the heat generation of the plasmon nanostructure. This work investigates the influence of the thermoplasmonic effect of gold nanobrick antenna on the optical capture of nanoparticles. Due to the enhancement of local electromagnetic field and strong heat generation of gold nanobrick antenna, various optothermo-matter interactions will occur. On this basis, the effects of optical, thermophoretic, and thermo-osmotic forces on the motion of Brownian nanoparticles are analyzed. Afterward, the factors that affect the capture efficiency are investigated. The results indicate that the photothermal effect of nanobrick antenna can reduce the capture efficiency of nanoparticles. In addition, increasing the refractive index or diameter of nanoparticles, thermal conductivity of the substrate, and incident laser power can improve the capture efficiency.